Why EU promotion is at odds with successful crisis management : public relations, news coverage, and the Aceh Monitoring Mission - Anderson, Stephanie (2014)
The EU’s Common Foreign and Security Policy (CFSP) and its accompanying Common Security and Defence Policy (CSDP) missions can be tools used to increase the international profile of the European Union. Nevertheless, CSDP missions garner little news coverage. This article argues that the very nature of the missions themselves makes them poor vehicles for EU promotion for political, institutional, and logistical reasons. By definition, they are conducted in the middle of crises, making news coverage politically sensitive. The very act of reporting could undermine the mission. Institutionally, all CSDP missions are intergovernmental, making press statements slow, overly bureaucratic, and of little interest to journalists. Logistically, the missions are often located in remote, undeveloped parts of the world, making it difficult and expensive for European and international journalists to cover. Moreover, these regions in crisis seldom have a thriving, local free press. Using the Aceh Monitoring Mission (AMM) as a case study, the author concludes that although a mission may do good, CSDP missions cannot fulfil the political function of raising the profile of the EU.